Integração de animações em Python no ensino de Física: um estudo sobre tecnologias multimídia no Ensino Médio - SOUSA SOBRINHO, Fábio José de (2024)
This work presents an didactic proposal for teaching Physics in high school, utilizing animations developed through the Manim library in the Python programming language. The central challenge of the study lies in the difficulty students face in visualizing and understanding abstract concepts in Physics using traditional methods, especially in a context where there is little integration of digital technologies in classrooms. The research was conducted in two classes of 2nd and 3rd-year high school students, totaling 31 learners, at Colégio Aspecto, located in Ananindeua, Pará. The methodology involved administering questionnaires to assess students' perceptions of using programming in Physics classes, comparing the effectiveness of traditional teaching methods with the use of interactive animations. The main contributions of integrating Information and Communication Technologies (ICT) in teaching Physics include the introduction of animations as a pedagogical tool to facilitate the visualization of physical concepts, promoting greater student engagement and cognitive development. The results indicated that animations were essential for improving content comprehension, making lessons more dynamic and accessible. As a key outcome, students reported an increase in interest and engagement with the use of programming, highlighting the role of animations in facilitating the learning of complex concepts in Physics.